(untitled) (European Bison Conservation Newsletter, 2009)
The objective of the study was to compare two methods used to determine serum levels of total testosterone (TT) in European bison Bison bonasus (Linnaeus, 1758) males: the radioimmunological method (RIA) and the immunoenzymatic method (ELISA). The study material included sera from 83 European bison males aged 2 months – 19 years, which were culled in the autumn and winter periods (in the post-rutting season), in the years 1993–2002, in the Białowiez˙a Primeval Forest. TT levels were determined using the two methods (RIA and ELISA) in the same animals. The following age groups were distinguished: class I – calves under the age of 1 year, class II –juveniles under the age of 2 years, class III –juveniles under the age of 3, class IV – adult males aged 4–5 years, class V – adult males aged 6–12 years, class VI-old bulls over the age of 12. In our study, serum TT levels measured using the RIA method were lower, higher or similar in comparison with those determined by ELISA in the same animals, although higher concentrations were more frequent when the ELISA method was used. With the RIA method, we obtained 26 results (31.30%) below the bottom limit for this method, i.e. 0.14ng/ml. Included in this number there were 18 animals in class I (56.25%), 6 in class II (37.50%), 1 in class III (14.28%) and 1 in class V (11.11%). The mean serum levels of TT determined by ELISA were higher than those obtained using RIA in the same age classes, the difference being statistically significant in class I and II (p<0.001), and on the border of statistical significance in class IV and VI (p<0.088 and p<0.047, respectively).